ANALYSIS OF THE ENVIRONMENTAL FIELD PHILOSOPHY COURSES AT THE OMORA ETNOBOTANICO PARK, BIOSPHERE RESERVE CABO DE HORNOS, CHILE - Malebran, Javiera; Rozzi Marin, Ricardo Roberto (My University, 2018)
One of the drivers of the global socio-environmental change is the growing rate of urbanization, with more than half of the world's population living in urban environments. This trend fosters biocultural homogenization throughout the world and results in a disconnection between society and natural environments and, therefore, a lack of knowledge about the biocultural diversity associated to them. The concentration of the population in the cities generates a disconnection between society and natural environments, and a lack of knowledge of the biocultural diversity associated with them. This disconnection fosters processes of biocultural homogenization around the world. At the Omora Ethnobotanical Park, the southernmost site of the Chilean network of Long-Term Socio-Ecological Research (LTSER) sites, a methodological approach has been developed that through research, education and conservation practices aims to remedy this disconnection and lack of empathy: Field Environmental Philosophy (FEP). This methodology seeks to foster a sense of concern, care and protection of biocultural diversity, and reverse the global trend towards a biocultural homogenization. This article focuses on the international FEP course that takes place annually at Omora Park, examining the courses that were offered in 2015, 2016, 2017 and 2018. Participants from different regions of the world and different disciplines immerse themselves in an academic, natural, social and institutional environment. They live intercultural and interdisciplinary experiences that guide a transformation in the ways of observing, understanding and valuing biocultural diversity, learning and apprehending different and new points of view. Participants recover essential practices for naturalists and managed to integrate the biophysical and cultural dimensions involved in biocultural research, education, and conservation. This integration considers the points of view of science, philosophy and the arts, as well as the areas of professional and personal development of each participant. The potential for application of similar field courses in other sites of long-term socio-ecological studies and conservation areas in the world is discussed, and how these sites could contribute to a reconnection of students and other social groups with the biocultural diversity of their regions.
Keywords: environmental education; natural history; environmental ethics; interdisciplinary; intercultural